THE IMPORTANCE OF SECTORAL INTERLOCKING OF THE MANUFACTURING INDUSTRY IN ACHIEVING ECONOMIC DEVELOPMENT IN IRAQ - Mohammed Kadhim Shamkhi (Scholar Express Journals, 2024)
The sectoral interconnection of the manufacturing industry is of great importance in the national economy, as it shows the level of forward and backward interdependence between the branches of the manufacturing industry, The topic also acquires importance by standing on the nature of the overlapping relationships between economic activities and knowing the levels of this overlap. The index of forward and backward links for the manufacturing sector recorded fluctuating and unstable data, and the reason is the ineffectiveness of manufacturing activities and its weak contribution to the GDP. This conclusion comes from the state's orientation and dependence on the outside world and the opening of the door to import, and thus the decline of the local industry to the level that this study came out with. The best evidence for this is what the study found of a significant weakness in the front and back pull links of the manufacturing sector with other economic activities
Keywords: Sectorial entanglement; Manufacturing industry; Economic development